2004
DOI: 10.1007/s11103-004-6324-z
|View full text |Cite
|
Sign up to set email alerts
|

Gamma carbonic anhydrase like complex interact with plant mitochondrial complex I

Abstract: We report the identification by two hybrid screens of two novel similar proteins, called Arabidopsis thaliana gamma carbonic anhydrase like1 and 2 (AtgammaCAL1 and AtgammaCAL2), that interact specifically with putative Arabidopsis thaliana gamma Carbonic Anhydrase (AtgammaCA) proteins in plant mitochondria. The interaction region that was located in the N-terminal 150 amino acids of mature AtgammaCA and AtgammaCA like proteins represents a new interaction domain. In vitro experiments indicate that these protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 41 publications
3
82
0
Order By: Relevance
“…Single-particle electron microscope imaging analysis of isolated CI from Arabidopsis and Polytomella identified a specific matrix-exposed domain formed by ␥-carbonic anhydrase (␥-CA) subunits that are attached to the membrane arm of mitochondrial CI by the integral membrane protein CA2 (5). In Arabidopsis, this protein domain contains at least three different ␥-CA proteins, CA1 (At1g19580), CA2 (At1g47260), and CA3 (At5g66510), having conserved active site regions, and two less well conserved ␥-CA-like proteins, CAL1 (At5g66510) and CAL2 (At3g48680), which contain alterations to the primary structure of typical ␥-CAs (6). Links between these subunits and photosynthetic function have been postulated (7), a role in photomorphogenesis in plants has been shown by gene knock-out studies (8), and overexpression leads to male sterility in plants (9), but a CA activity from these proteins has not been experimentally confirmed.…”
Section: Nadh-ubiquinone Oxidoreductase (Complex I (Ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…Single-particle electron microscope imaging analysis of isolated CI from Arabidopsis and Polytomella identified a specific matrix-exposed domain formed by ␥-carbonic anhydrase (␥-CA) subunits that are attached to the membrane arm of mitochondrial CI by the integral membrane protein CA2 (5). In Arabidopsis, this protein domain contains at least three different ␥-CA proteins, CA1 (At1g19580), CA2 (At1g47260), and CA3 (At5g66510), having conserved active site regions, and two less well conserved ␥-CA-like proteins, CAL1 (At5g66510) and CAL2 (At3g48680), which contain alterations to the primary structure of typical ␥-CAs (6). Links between these subunits and photosynthetic function have been postulated (7), a role in photomorphogenesis in plants has been shown by gene knock-out studies (8), and overexpression leads to male sterility in plants (9), but a CA activity from these proteins has not been experimentally confirmed.…”
Section: Nadh-ubiquinone Oxidoreductase (Complex I (Ci)mentioning
confidence: 99%
“…Conservation and Losses of 20.9, ␥-CA, and ␥-CAL Proteins among Eukaryotic Lineages-Although ␥-CAs were initially considered plant-specific subunits of CI (6,10,11), more recent work has demonstrated the widespread occurrence of ␥-CA homologs throughout eukaryotes, with the notable exception of opisthokonts (animals ϩ fungi) (12). Extending this analysis, we have found that in organisms in which deep genome and/or transcriptome sequencing has been performed, multiple ␥-CA genes are often found (Table 1 and supplemental Data Set S4).…”
Section: Ca2 Is Imported and Assembled Into A Transient 200-kda Subcomentioning
confidence: 99%
“…The active unit of the bCA is a dimer where the active site is located at the interface of the two monomers (Kimber and Pai, 2000). In contrast, gCAs are trimers that have their active site zinc ion situated at the interface of two subunits coordinated by His residues from both subunits (Kisker et al, 1996;Iverson et al, 2000).In Arabidopsis (Arabidopsis thaliana), there are three gCA proteins and two g-like proteins that interact to form an extra structure of complex I of the mitochondrial electron transport chain (Perales et al, 2004;Sunderhaus et al, 2006). Although not active in vitro, gCA has been shown to bind inorganic carbon (Martin et al, 2009), affect complex I levels, plant growth, and gas-exchange rates when deleted (Perales et al, 2004;Soto et al, 2015), and cause plant sterility when ectopically overexpressed ).…”
mentioning
confidence: 99%
“…In Arabidopsis (Arabidopsis thaliana), there are three gCA proteins and two g-like proteins that interact to form an extra structure of complex I of the mitochondrial electron transport chain (Perales et al, 2004;Sunderhaus et al, 2006). Although not active in vitro, gCA has been shown to bind inorganic carbon (Martin et al, 2009), affect complex I levels, plant growth, and gas-exchange rates when deleted (Perales et al, 2004;Soto et al, 2015), and cause plant sterility when ectopically overexpressed ).…”
mentioning
confidence: 99%
See 1 more Smart Citation